Modelos alométricos para estimativa da produção de frutos em Jatropha curcas L. - Ignácio, Vanessa Leonardo (2009)
The objective was to correlate easy measurement variables and determine various regression equations to achieve allometric patterns in culture of pinion manso (Jatropha curcas L.). Thus, two different spacings (3 x 2 m 5 x 2 m) were compared to obtain the data that best represent the culture. Data collection occurred in the municipality of Eldorado-MS. The correlated variables were: total height of the plant (ALT), number of primary branches (NG), average diameter of primary branch (DG), total number of leaves per plant (NFL), leaf area (LPA), total number of fruits (NF) and fresh mass of fruit (MF). Comparing the average of spacing, the variables height and number of primary branches did not show significant difference, while all others did. For the spacing 5 x 2 m, the correlations were higher compared with the spacing 3 x 2 m. For variable number of fruits in function of the number of leaves and plant height the models that stood out were: NFtotal = -599.046 + 0.4549 + 0.00025 NFL2 NFL ALT + 300.032 - 0.3185 * NFL ALT for treatment 1 and NFtotal = -201.106 - 0.3691 + 0.000179 NFL NFL2 + 170.389 ALT for treatment 2. For other variables, the correlation that most stood out was between leaf area and number of leaves which the models stood out from logarithmic equations